PENGARUH MODEL PROJECT BASED LEARNING TERHADAP MATERI PERUBAHAN WUJUD BENDA TERHADAP HASIL BELAJAR IPAS DI SEKOLAH DASAR - Panni Ance Lumbantobing; Rumiris Lumbangaol; Restio Sidebang; Eva Farida; Edy Surya (JS (JURNAL SEKOLAH), 2026)
Abstract: This study aims to determine the effect of the Project Based Learning model on the IPAS learning outcomes of fourth-grade students at UPT SDN 064983 Medan Helvetia on the topic of changes in the states of matter. The research method used was quantitative with a pre-experimental design, namely a one-group pretest–posttest design. Data were collected through tests administered before and after the treatment. The sample consisted of all fourth-grade students totaling 28 learners. Data analysis showed that the average pretest score was 58.21, which increased to 81.43 on the posttest. The normality test indicated that the data were normally distributed, allowing for further analysis using a paired t-test. The t-test results showed a significance value of 0.000, which is less than 0.05, and a t-count of 8.638, which is greater than the t-table value of 2.048. Therefore, it can be concluded that there is a significant difference between the pretest and posttest scores. Additionally, the N-Gain test results showed that most students were in the medium category. The Project Based Learning model is effective in improving the IPAS learning outcomes of fourth-grade students on the topic of changes in the states of matter. Keywords: Project Based Learning, Collaboration, Relevance. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model Project Based Learning terhadap hasil belajar IPAS siswa kelas IV UPT SDN 064983 Medan Helvetia pada materi perubahan wujud benda. Metode penelitian yang digunakan adalah kuantitatif dengan desain pra-eksperimental, yaitu one-group pretest–posttest design. Data dikumpulkan melalui tes sebelum dan sesudah perlakuan. Sampel penelitian adalah seluruh siswa kelas IV yang berjumlah 28 orang. Hasil analisis menunjukkan nilai rata-rata pretest sebesar 58,21 dan meningkat menjadi 81,43 pada posttest. Uji normalitas menunjukkan data berdistribusi normal sehingga analisis dilanjutkan dengan uji t berpasangan. Hasil uji t menunjukkan nilai signifikansi sebesar 0,000 < 0,05 dan nilai t hitung sebesar 8,638 > t tabel 2,048. Dengan demikian, terdapat perbedaan yang signifikan antara nilai pretest dan posttest. Hasil uji N-Gain menunjukkan sebagian besar siswa berada pada kategori sedang. Model Project Based Learning terbukti efektif dalam meningkatkan hasil belajar IPAS siswa kelas IV pada materi perubahan wujud benda.   Kata kunci: Project Based Learning, kolaborasi, relevansi.